Frequency of Hyponatremia in Patients with Acute Stroke in Ayub Teaching Hospital Abbottabad - Jamil Ur Rahman; Ahmad, Tauqir; Shakir Ullah; Hussain, Mubasir; Haleem Ur Rahman; Bashar, Noor (Indus Journal of Bioscience Research, 2025)
Background: Stroke is a serious neurological condition and is one of leading causes of death and disability. Disturbance in serum sodium is common in acute stroke and may worsen neurological outcome. Objective: To determine the frequency of hyponatremia in patients with acute stroke admitted in a tertiary care hospital. Study Design: Cross sectional study. Duration and Place of Study: This study was carried out from 1 January 2024 to 1 July 2024 in medical ward of Ayub Teaching Hospital Abbottabad. Methodology: A total of 120 patient aged more than 40 years of both gender with clinical and computed tomography confirmed stroke were included. Hyponatremia was defined as serum sodium level less than 135 millimole per liter. Data were analyzed by Statistical Package for Social Sciences version 22. Stratification was done and post stratification chi square test and Fisher exact test were applied. A p value ≤0.05 was taken as significant. Results: Mean age was 62.00 ± 10.32 years. Mean serum sodium level was 135.65 ± 7.28 millimole per liter. Majority were male 84 (70.0%) and ischemic stroke was seen in 92 (76.7%) patients. Hyponatremia was found in 37 (30.80%) patients. No significant association was observed with age (p=0.183), gender (p=0.365), or stroke type (p=0.218). Conclusion: Hyponatremia is frequent in acute stroke patients and need early identification and management.